Development of a Mechanical Image Stabilization Method to Counter-act Rotational Disturbances - Karlsson,Oskar (CODEN:LUTEDX/TEIE, 2025)
Image stabilization is critical in producing usable footage recorded by Body-worn Cameras, which are subject to external disturbances caused by biomechanical factors, such as body movement while walking and running. The thesis work is carried out by first defining the nature of the disturbances upon which stabilization techniques are investigated, by reviewing literature and by gathering data using image analysis and sensor information. An active system is designed and prototyped, utilizing sensors and an actuator, controlled by a micro-controller. This system is designed to reduce the disturbances caused by the rotational movement of the upper torso. The work includes selection of an actuator system and the necessary control system components and sensors, a software implementation and mechanical design. After the active system is implemented, design and testing of a passive system is done. This passive system was initially thought to dampen the disturbances due to reciprocating motion of the camera housing, but the difference was negligible. The passive system does however provide support for the camera housing by providing a firm attachment between the camera and mounting solution, thus reducing disturbances. Lastly, an alternative to the actuator used in the active system is explored. This actuator conceptualization is supported by simulations and calculations, providing a foundation for a new actuator. This thesis provides methods for stabilizing a body-worn camera with accompanying methods for evaluating efficiency of methods. Active, passive, and combined image stabilization systems have been compared to a system without stabilization and the results are as follows: The largest increase in horizontal stability is achieved by employing an active system, reducing the horizontal displacement of the video feed by 69.5%. The largest increase in vertical stability is achieved by a passive damping mechanism, reducing the vertical displacement of the video feed by 15%. Combining the two and using a stiff damping material results in a 66% reduction in displacement horizontally, and 44.5% reduction in vertical displacement.
Keywords: Mechanical Image Stabilization; Body-worn Camera; Actuator; Image Analysis